SPANISH INVESTMENT IN LATIN AMERICA IN THE FACE OF NEW CHALLENGES - T. . Sidorenko (Ибероамериканские тетради, 2016)
The article analyzes the main directions of expansion and location of Spanish multinationals in the economies of Latin America in the late XX - early XXI centuries. Particular attention is paid to the identification of the competitive advantages of Spanish companies, which would allow them to strengthen their position in the markets of Latin American countries in the post-crisis period.